New Visions of Adolescence in Contemporary Latin American Cinema (New Directions in Latino American Cultures, 2018)
This volume explores the recent 'adolescent turn' in contemporary Latin American cinema, challenging many of the underlying assumptions about the nature of youth and distinguishing adolescence as a distinct and vital area of study. Its contributors examine the narrative and political potential of teenage protagonists in a range of recent films from the region, acknowledging the distinct emotional registers that are at play throughout adolescence and releasing teenage subjectivities from restrictive critical and theoretical emphases on theories of childhood. As the first academic study to examine the figure of the adolescent in contemporary Latin American film, New Visions of Adolescence in Contemporary Latin American Cinema thus presents a timely and innovative analysis of issues of sexuality and gender, political and domestic violence and social class, and will be of significant interest to students and researchers in Latin American Studies, Cultural Studies, World Cinema and Childhood Studies.